2018
DOI: 10.1016/j.toxrep.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of Moringa peregrina seeds on histological and biochemical analyses of adult male Albino rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Also, other phytoconstituents such as β-sitosterol could be the major cholesterol reducing components of Moringa oleifera leaf ethanol extract as it may work singly or in synergy with other bioactive agents (Pop et al, 2018), which may be the cause improvement of lipid profile in this study. Similar results are recorded in rats administered different levels of dry seed of M. peregrina by El-Hak et al (2018).…”
Section: Biochemical Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…Also, other phytoconstituents such as β-sitosterol could be the major cholesterol reducing components of Moringa oleifera leaf ethanol extract as it may work singly or in synergy with other bioactive agents (Pop et al, 2018), which may be the cause improvement of lipid profile in this study. Similar results are recorded in rats administered different levels of dry seed of M. peregrina by El-Hak et al (2018).…”
Section: Biochemical Findingssupporting
confidence: 85%
“…Regarding to the serum liver enzymes, goats fed MOSM at the levels of 25 and 50% (G2&G3) showed significant decreased of the ALT and AST activities during the different periods. This effect could be attributed to its content of vitamins, carotenoids and phytocompounds; polyphenols, phenolic acids, flavonoids, alkaloids, glucosinolates, isothiocyanates, tannins and saponins which have been proved to have potent antioxidant properties and other biological activities (Zade et al, 2013;Idoko et al, 2017;El-Hak et al, 2018;Atta et al, 2019).…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…Although M. peregrina seeds have been reported to be widely used in traditional medicine, only a few scientific studies exist on its therapeutic efficacy and mechanism of action. 11,14,18,19 As a follow-up to those studies, our aim was to investigate the effects of MPSE, which may be considered a potential antiinflammatory drug, on NO and IL-1β in LPS-induced J774A.1 macrophage cells. Macrophages are the predominant cells in immunologic responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also administered to pregnant women to facilitate fetus delivery. 11 Pharmacological studies have reported the validation of this plant for antiinflammatory, antimicrobial, antiulcer, and antioxidant use. 10,12 M. peregrina seed oil contains high amounts of oleic acid, linoleic acid, tocopherols, and phenolic compounds, which help to reduce inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Rats were sacrificed by decapitation. Part of the forebrains, heart, lung, liver, kidney, spleen, stomach, small intestine epidydimis, testes, uterus and ovary were isolated and fixed in 10 % of phosphate buffered formalin for 2 days for histological preparation for light microscopic examination [EL-Hak, Moustafa [15,16,17]. 0.5 g of each rat tissue was used for the assessment of aluminum concentrations [18].…”
Section: Experimental Designmentioning
confidence: 99%